EARLY PREGNANCY OF JUNIOR HIGH SCHOOL GIRLS: CAUSES AND IMPLICATIONS ON ACADEMIC PROGRESSION IN THE TALENSI DISTRICT OF THE UPPER EAST REGION OF GHANA - Alhassan, E. (UDS International Journal of Development, 2016)
Early pregnancy by teenagers has recently become a topic for discussion in Ghana and has eventually gained media attention. Its occurrence has become very frequent, making one to wonder if the sex education campaigns by the government, NGOs as well as the media always fall on deaf ears.Â Pregnancy and birth rates among teenagers in Ghana and its accompanying social, physical, behavioral, economic, and educational consequences for the teenage mothers and the society have prompted many initiatives to prevent adolescent pregnancy. The study examined the socio-economic causes of early pregnancy, psychological causes as well as its implications in Talensi District of the Upper East Region of Ghana. Non-pregnant and pregnant teenage girls were selected using probability and non-probability ssampling techniques. Data was collected through semi-structured interview schedules and structured questionnaires and analyses were done with the help of the Statistical Package for Social Sciences involving frequency tables, percentages as well as charts. The results showed that cell phone usage by teenagers, inadequate contraceptives, peer group influence, family neglect and poverty had a negative and detrimental effect on teenagersâ€™ academic career, increased family burden and sexual transmitted diseases. The study recommended that sex and sexuality learning programmes should be introduced in JHS, ban the open dances at funeral centers and provide contraceptives at vantage points, establishment of youth centers and finally, establishment of parent information sessions in various communities of the district. These would go a long way to reduce the incidence of early pregnancy in the district. Â Keywords: Early Pregnancy, Socio-Economic factors, Psychological Factors, Poverty, and Education.Â